The novel chlamydial adhesin CPn0473 mediates the lipid raft‐dependent uptake of Chlamydia pneumoniae. (21st February 2016) - Fechtner, Tim; Galle, Jan N.; Hegemann, Johannes H.
Summary: Chlamydiae are Gram‐negative, obligate intracellular pathogens that pose a serious threat to public health worldwide. Chlamydial surface molecules are essential for host cell invasion. The first interaction with the host cell is thereby accomplished by the Outer membrane complex protein B (OmcB) binding to heparan sulfate moieties on the host cell surface, followed by the interaction of the chlamydial polymorphic membrane proteins (Pmps) with host cell receptors. Specifically, the interaction of the Pmp21 adhesin and invasin with its human interaction partner, the epidermal growth factor receptor, results in receptor activation, down‐stream signalling and finally internalization of the bacteria. Blocking both, the OmcB and Pmp21 adhesion pathways, did not completely abolish infection, suggesting the presence of additional factors relevant for host cell invasion. Here, we show that the novel surface protein CPn0473 of Chlamydia pneumoniae contributes to the binding and invasion of infectious chlamydial particles. CPn0473 is expressed late in the infection cycle and located on the infectious chlamydial cell surface. Soluble recombinant CPn0473 as well as rCPn0473‐coupled fluorescent latex beads adhere to human epithelial HEp‐2 cells. Interestingly, in classical infection blocking experiments pretreatment of HEp‐2 cells with rCPn0473 does not attenuate adhesion but promotes dose‐dependently internalization by C. pneumoniae suggesting an unusual mode of action for this adhesin. This CPn0473‐dependent promotion of infection by C. pneumoniae depends on two different domains within the protein and requires intact lipid rafts. Thus, inhibition of the interaction of CPn0473 with the host cell could provide a way to reduce the virulence of C. pneumoniae .